LEADERSHIP AND ORGANIZATIONAL CULTURE ANALYSIS ON ORGANIZATIONAL CITIZENSHIP BEHAVIOR (OCB) AT PT. HATTEN BALI - Ni K Irma Ariyanti; I K Santra I K Santra; Ni K Lasmini Ni K Lasmini; Ni.K Narti Ni.K Narti; CGP Yudistira CGP Yudistira; K. M. Putra K. M. Putra (Fakultas Ekonomi dan Bisnis Universitas Atma Jaya Makassar, 2018)
This study aimed to analyze the influence of leadership and organizational cultureon Organizational Citizenship Behavior employees. The study is a quantitativeresearch. The data used in this study was collected through questionnaires andimplemented to 106 of permanent employees in PT. Hatten Bali. The results ofthis study indicates that: 1) Leadership have positive and significant effect onorganizational citizenship behavior which indicated by coefficient regressionvalue 0,297 and significant value 0,003. 2) Organizational culture have positiveand significant effect on Organizational Citizenship Behavior which indicated bycoefficient regression value 0,144 and significant value 0,039. 3) Leadership andorganizational culture have simultaneously effect on organizational citizenshipbehavior which indicated by f-count value 6,846 > f-table and significant value0,002. Regression analyze result adjusted R2 value 0,117. This indicates thatorganizational citizenship behavior can explained by leadership andorganizational culture variable of 11,7 % while the remaining 88,3% explained bythe others variable outside of this study.